Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3389/fsurg.2022.850378
|View full text |Cite
|
Sign up to set email alerts
|

Which Role for Hyperbaric Oxygen Therapy in the Treatment of Fournier's Gangrene? A Retrospective Study

Abstract: PurposeIn Fournier's gangrene, surgical debridement plus antimicrobial therapy is the mainstay of treatment but can cause a great loss of tissue. The disease needs long hospital stays and, despite all, has a high mortality rate. The aim of our study is to investigate if factors, such as hyperbaric therapy, can offer an improvement in prognosis.MethodsWe retrospectively evaluated data on 23 consecutive patients admitted for Fournier's gangrene at the University Hospital “P. Giaccone” of Palermo from 2011 to 201… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Of the ten studies, Creta et al and Feres et al have notable significance in the analysis due to the larger number of samples compared to other studies (7,10). Only two studies reported an increase in mortality in patients treated with HBOT (13,18).…”
Section: Meta-analysis Results On Mortalitymentioning
confidence: 98%
See 1 more Smart Citation
“…Of the ten studies, Creta et al and Feres et al have notable significance in the analysis due to the larger number of samples compared to other studies (7,10). Only two studies reported an increase in mortality in patients treated with HBOT (13,18).…”
Section: Meta-analysis Results On Mortalitymentioning
confidence: 98%
“…Based on the analysis of ten included studies (7,(10)(11)(12)(13)(14)(15)(16)(17)(18), patients with HBOT have a significantly lower mortality rate than patients without HBOT (OR 0.29; 95%CI 0.12, 0.69; p=0.005) (Figure-2). The random-effects model was used due to high heterogeneity between studies (P = 0.03; I 2 = 51%).…”
Section: Meta-analysis Results On Mortalitymentioning
confidence: 99%
“…All 23 studies [ 3 , 7 , 19 – 39 ] included were retrospective studies with a total of 49,152 patients, and 1448 patients were treated HBO, versus 47,704 patients treated without HBO. Ten studies came from North America (8 from USA, 2 from Canada).…”
Section: Resultsmentioning
confidence: 99%
“…We did a subgroup analysis with pathological entity into two categories: FG subgroup and Non-FG subgroup. The FG subgroup consisted of 10 studies [ 7 , 19 21 , 24 , 25 , 30 , 33 , 35 , 36 ]. The Non-FG consisted of 13 studies [ 3 , 22 , 23 , 26 – 29 , 31 , 32 , 34 , 37 – 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…HBOT can increase the oxygen partial pressure of tissues and organs, and promote wound recovery through various mechanism. 100 HBOT is especially suitable for FG patients who are unresponsive to conventional treatment, complicated with Clostridium or anaerobes and deep tissue involvement. 101 Although few studies reported an increase in mortality, most studies showed that HBOT has a beneficial effect in the prognosis of FG.…”
Section: Hyperbaric Oxygen Therapy (Hbot)mentioning
confidence: 99%